The Interplay of ESG Performance and Global Supply Chains: An Input-Output Study of China, Japan, and the United States - Xie, Jun; Unal, Emre; Keeley, Alexander Ryota; Managi, Shunsuke (Wiley, 2026)
This study examines how supply-chain dependencies are associated with industry-level ESG performance trajectories in China, Japan, and the United States over the period 2000-2021. Drawing on stakeholder and institutional theories, we adopt a meso-level perspective that conceptualizes industries as structural units embedded within national production systems. An empirical framework combining multiregional input-output linkage measures and convergence analysis is applied to assess the roles of domestic consumption-based and export-oriented supply-chain dependencies. The results show that supply-chain dependencies are systematically associated with environmental performance trajectories, whereas no comparable patterns are observed for social and governance dimensions. Domestic linkages play a more salient role than export-oriented linkages, although their associations vary across institutional contexts. Complementary industry-level case analyses reveal substantial sectoral heterogeneity, illustrating how differences in demand composition and production network positions shape ESG outcomes. Overall, the findings highlight the contingent role of supply-chain structures in shaping industrial sustainability trajectories.
Keywords: Backward And Forward Linkages; Esg Performance; Sensitivity Analyses; Supply Chains